A high-quality chromosome-scale genome assembly of Xingan mandarin (Citrus reticulata ‘Xingan’), a primitive Mandarin type - Chongling Deng; Xiaoxiao Wu; Yan Tang; Haimeng Fang; Chuanwu Chen; Ping Liu; Jing Feng; Shengqiu Liu; Xiaoqiang Guo (Scientific Data)
Abstract Mandarin (Citrus reticulata) is broadly recognized as one of the foremost citrus crops globally. Our study identified the Xingan mandarin (Citrus reticulata ‘Xingan’) as a primitive type found near Maoer Mountain. This report provides a high-resolution, chromosome-scale genome assembly for the Xingan mandarin. The total size of the genome assembly is an impressive 325.12 Mb, including contig N50 and scaffold N50 values of 29.32 Mb and 29.62 Mb, respectively. Notably, we successfully anchored approximately 93.08% of the assembled sequences onto nine pseudochromosomes. Our predictions identified 30,581 protein-coding genes, 166 miRNAs, 415 tRNAs, 728 rRNAs, 325 snRNAs, and 659 snoRNAs. We were able to predict the functions of 27,242 genes, constituting 89.08% of the total protein-coding genes. A notable finding of our study was the high degree of genome synteny between the Xingan mandarin and the Mangshan mandarin (Citrus reticulata ‘Mangshan’), reinforcing their genetic similarity. The acquisition of the chromosome-level genome for the Xingan Mandarin represents a significant milestone, laying an indispensable foundation for rigorous molecular investigations of this species. Moreover, it is poised to invigorate advanced research in comparative genomics within the Citrus genus.